Oceans 2003. Celebrating the Past ... Teaming Toward the Future (IEEE Cat. No.03CH37492) 2003
DOI: 10.1109/oceans.2003.178629
|View full text |Cite
|
Sign up to set email alerts
|

Buried object scanning sonar for AUVs

Abstract: Abstrocf-A 252 channel FM sonar is developed to generate images of objects buried in sediments using reflection tomography. An omnidirectional source, transmitting FM pulses over the band of 2 to 12 IrHz, illuminates buried targets.The backscattered signals are measured with 252 hydrophones and processed with a digital matched filter. Coherent nearfield focusing generates a 3D map of acoustic intensity for each transmission event. As the sonar approaches and passes buried targets, the processor generates 3D ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Target backscattering is measured by the 252 hydrophones (or a subset) and is then processed by a CPU to generate a final composite image. BOSS processing involves a sequence of operations that includes chirp sonar processing, 3-D near field focusing using data from a real or synthetic receiving aperture, transmission beam steering that allows target illumination at a broad range of aspect angles, real-time 3-D image construction of buried objects showing burial depth, shape, and orientation and location of buried objects, and real-time buried object detection [9].…”
Section: Boss System and Data Collectionmentioning
confidence: 99%
“…Target backscattering is measured by the 252 hydrophones (or a subset) and is then processed by a CPU to generate a final composite image. BOSS processing involves a sequence of operations that includes chirp sonar processing, 3-D near field focusing using data from a real or synthetic receiving aperture, transmission beam steering that allows target illumination at a broad range of aspect angles, real-time 3-D image construction of buried objects showing burial depth, shape, and orientation and location of buried objects, and real-time buried object detection [9].…”
Section: Boss System and Data Collectionmentioning
confidence: 99%
“…This was accomplished by maintaining a constant transmitter and receiver grazing angle as the BOSS vehicle was towed over the target field. In these studies, it was found that different grazing angles provided unique shape information about the target, and hence it was concluded that a wide variety of grazing angles should be used during image construction to capture the shape of the buried object [12].…”
Section: Boss System and Data Collectionmentioning
confidence: 99%
“…Target backscattering is measured by the 252 hydrophones (or a subset of these) and is then processed by a CPU to generate a final composite image. BOSS processing involves a sequence of operations that includes chirp sonar processing, 3D nearfield focusing using data from a real or synthetic receiving aperture, transmission beam steering that allows target illumination at a broad range of aspect angles, real time 3D image construction of buried objects showing burial depth, shape, and orientation and location of buried objects, and real-time buried object detection [12].…”
Section: Boss System and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous publications on BOSS processing discuss strip-map [1] and multi-aspect processing [2,3] based on time-delay focusing of data from a large aperture hydrophone array. In these approaches the resolution of target imagery is limited by the dimensions of the hydrophone array.…”
Section: I Introductionmentioning
confidence: 99%